Monitoring of thermal comfort and air quality for sustainable energy management inside hospitals based on online analytical processing and the internet of things - Garcés, Hugo O.; Durán, Claudia A.; Espinosa, Eduardo; Jerez, Alejandro; Palominos, Fredi; Hinojosa, Marcela; Carrasco Armijo, Raúl Vicente. (MDPI, 2022)
There is a need to ensure comfortable conditions for hospital staff and patients from the point of view of thermal comfort and air quality so that they do not affect their performance. We consider the need for hospital employees and patients to enjoy conditions of greater well-being during their stay. This is understood as a comfortable thermal sensation and adequate air quality, depending on the task they are performing. The contribution of this article is the formulation of the fundamentals of a system and platform for monitoring thermal comfort and Indoor Air Quality (IAQ) in hospitals, based on an Internet of Things platform composed of a low-cost sensor node network that is capable of measuring critical variables such as humidity, temperature, and Carbon Dioxide (CO2). As part of the platform, a multidimensional data model with an On-Line Analytical Processing (OLAP) approach is presented that offers query flexibility, data volume reduction, as well as a significant reduction in query response times. The experimental results confirm the suitability of the platform’s data model, which facilitates operational and strategic decision making in complex hospitals.
Keywords: Thermal comfort; Calidad del aire; Hospitales; Internet de las cosas